Contextual Factors Affecting Risky Decision Making: The Influence of Music on Task Performance and Perceived Distraction - Buelow, Melissa T.; Jungers, Melissa K.; Parks, Cora; Rinato, Bonnie (Frontiers in Psychology, 2022)
Previous research has investigated factors that contribute to the development of different risk-taking behaviors, such as can occur on lab-based behavioral risky decision making tasks. On several of the most common tasks, participants must develop an adequate understanding of the relative risks and benefits associated with each decision in order to learn to decide advantageously. However, contextual factors can affect the decision making process and one’s ability to weigh the risks and benefits of a decision. The present study investigates the extent to which music may be an additional contextual factor that can disrupt decision making and other executive functions. Across four studies we examine whether having music playing passively in the background or having participants actively listen to music affects performance on measures of risky decision making, working memory, processing speed, and problem solving. Participants reported greater distraction for rock music than classical music in the passive listening studies but did not report any differences in distraction across conditions in the active listening studies. Despite this self-reported increased level of distraction, few significant differences were found in task performance across groups and across studies. The Angling Risk Task was sensitive to differences in risk by condition, with music leading to greater risk-taking in a passive listening study, but less risk-taking in an active listening study, compared to no music. The extent to which music serves as a contextual factor disrupting performance on measures of risky decision making and other executive functions may depend in part on whether individuals are actively versus passively listening to the music.